Analysis of User Perspectives on Features of Regional Government Information System (SIPD RI) in Palu - Afrilia, Viki; Furqan, Andi Chairil; Karim, Fikry; Meldawati, Lucyani (Lembaga Riset Ilmiah, 2025)
This research seeks to examine how users perceive the functionalities of the Regional Government Information System of the Republic of Indonesia (SIPD RI) as implemented in Palu City. The analysis is grounded in the End-User Computing Satisfaction (EUCS) framework, which encompasses five core dimensions: Content, Accuracy, Format, Ease of Use, and Timeliness. A quantitative approach was employed by distributing structured questionnaires to 230 respondents, all of whom are SIPD RI users across 41 Regional Government Organizations (OPD) in Palu City. Data analysis was conducted using SPSS software, encompassing assessments of instrument validity and reliability, tests for normality, multicollinearity, and heteroscedasticity, as well as the application of multiple linear regression to evaluate relationships among variables. The findings indicate that, on a partial basis, the variables of Content, Accuracy, and Format exert a significant and positive influence on user satisfaction. In contrast, Ease of Use and Timeliness do not exhibit a statistically significant impact, although their contributions remain positive. The main limitation of this study lies in its scope, which is confined to SIPD RI users within Palu City, and in its reliance on a closed-ended questionnaire, which limits the exploration of users’ subjective experiences and perceptions. Nevertheless, the study provides valuable insights by identifying key aspects of SIPD RI that require improvement and offering practical recommendations for system developers and local governments to enhance the sustainable utilization of SIPD RI. This research seeks to examine how users perceive the functionalities of the Regional Government Information System of the Republic of Indonesia (SIPD RI) as implemented in Palu City. The analysis is grounded in the End-User Computing Satisfaction (EUCS) framework, which encompasses five core dimensions: Content, Accuracy, Format, Ease of Use, and Timeliness. A quantitative approach was employed by distributing structured questionnaires to 230 respondents, all of whom were SIPD RI users across 41 Regional Government Organizations (OPD) in Palu City. Data analysis was conducted using SPSS software, encompassing assessments of instrument validity and reliability, tests for normality, multicollinearity, and heteroscedasticity, as well as the application of multiple linear regression to evaluate relationships among variables. The findings indicate that, on a partial basis, the variables of Content, Accuracy, and Format exert a significant and positive influence on user satisfaction. In contrast, Ease of Use and Timeliness do not exhibit a statistically significant impact, although their contributions remain positive. The main limitation of this study lies in its scope, which is confined to SIPD RI users within Palu City, and in its reliance on a closed-ended questionnaire, which limits the exploration of users' subjective experiences and perceptions. Nevertheless, the study provides valuable insights by identifying key aspects of SIPD RI that require improvement and offering practical recommendations for system developers and local governments to enhance the sustainable utilization of SIPD RI.